2013
DOI: 10.1371/journal.pone.0072037
|View full text |Cite
|
Sign up to set email alerts
|

Replication and Meta-Analysis of GWAS Identified Susceptibility Loci in Kawasaki Disease Confirm the Importance of B Lymphoid Tyrosine Kinase (BLK) in Disease Susceptibility

Abstract: The BLK and CD40 loci have been associated with Kawasaki disease (KD) in two genome-wide association studies (GWAS) conducted in a Taiwanese population of Han Chinese ancestry (Taiwanese) and in Japanese cohorts. Here we build on these findings with replication studies of the BLK and CD40 loci in populations of Korean and European descent. The BLK region was significantly associated with KD susceptibility in both populations. Within the BLK gene the rs2736340-located linkage disequilibrium (LD ) comprising the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 19 publications
8
49
1
Order By: Relevance
“…Following this study, Japanese and Taiwanese studies also confirmed this genetic association while at the same time characterizing CD40 and BLK , respectively, as being associated with KD, as confirmed for BLK in Caucasian KD patients in a subsequent meta-analysis [12, 72, 94]. CD40 is a protein expressed on antigen-presenting cells, such as dendritic cells, macrophages, and B cells, and interacts with CD40L which is primarily expressed by activated T cells and platelets [49].…”
Section: Geneticssupporting
confidence: 53%
“…Following this study, Japanese and Taiwanese studies also confirmed this genetic association while at the same time characterizing CD40 and BLK , respectively, as being associated with KD, as confirmed for BLK in Caucasian KD patients in a subsequent meta-analysis [12, 72, 94]. CD40 is a protein expressed on antigen-presenting cells, such as dendritic cells, macrophages, and B cells, and interacts with CD40L which is primarily expressed by activated T cells and platelets [49].…”
Section: Geneticssupporting
confidence: 53%
“…Recent GWAS studies have discovered that several genetic polymorphisms (SNPs) are associated with increased risk for KD and CAA 58, 59 . Among these SNPs that are associated with increased risk for KD as well as risk for CAA, one that has attracted a major interest is found in the inositol 1,4,5,-triphosphate 3 kinase (ITPKC) gene 4, 6062 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, the International Kawasaki Disease Genetics Consortium performed a replication study in populations of Korean and European descent and confirmed the genetic contribution to KD pathogenesis by finding an association between B‐lymphoid tyrosine kinase ( BLK ) gene with KD . BLK is a Src family tyrosine kinase expressed primarily in the B‐cell lineage.…”
Section: Kawasaki Disease Featuresmentioning
confidence: 99%